Analysis of Physical Activity and Acculturation among Turkish Migrants in Germany and England. Issue 3 (December 2014) - Koca, Canan; Lapa, Tennur Yerlisu
Recent literature shows that migrant populations in Western countries are generally less physically active than their host populations. The purpose of the present study was to expand research investigating associations between physical activity (PA) and acculturation and their relationship with several socio-demographic factors among Turkish migrants in Germany and England. The sample consisted of 521 Turkish migrants. Migrant generation, length of residence, and language proficiency were used as indicators of acculturation. Acculturation was not associated with PA among migrants in Germany and England. PA of migrants was significantly associated with migrant's host country, age, sex, marital status, and education. The total PA of migrants in Germany was higher than that of migrants in England; the large majority of females in both Germany and England had low PA, whereas most males had moderate PA. Seemingly, PA in Turkish migrant populations will not necessarily increase as a result of greater acculturation to the host society.